PENGARUH COOPERATIVE LEARNING DIPANDU INQUIRY TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA BERKEMAMPUAN ATAS DAN BAWAH DI KOTA METRO - Handoko Santoso (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
The purpose of this research is to know the influence of biology teaching through inquiry integrated with cooperative towards the critical thinking ability. This research addresses the role of inquiry and cooperative learning strategy as well as these interactions towards the increase of the critical thinking ability. Quasi experimental research of Pretest-postest nonequivalent control group design with factorial design 2x2x2 were implemented on the odd semester in academic years of 2006/2007 on X grade student of the state SMA in Metro City Lampung. The research sample consists of 96 students, comprising of student from high and low academic abilities. To examine hypothesis, it is used Ancova technique and continued by LSD test. There was a difference on the critical thinking ability between students who learn by inquiry level 1 with student who learn by inquiry level 2, between students, who have high academic ability and students who have low academic ability, and there was not difference on the critical thinking ability between students who learn by STAD cooperative with student who learn by TPS. There is no effect of interaction between inquiry with cooperative, inquiry with student’s academic ability, cooperative with student’s academic ability, inquiry with cooperative and student’s academic ability towards the cognitive achievement Kata kunci: cooperative learning, inquiry, berpikir kritis